Development of sustainability framework for rural libraries in Malaysia / Siti Khadijah Rafie - Rafie, Siti Khadijah (2021)
Rural libraries which are often referred to as village or community libraries are developed to meet the needs of rural communities in Malaysia. The rural libraries are also found everywhere else in the world such as in China, Nigeria, Kenya, South America countries and many more. However, few rural libraries in other countries closed due to reasons such as underutilised and invisibility of sustainability plan which has been stated by previous studies. Therefore, this study identified the research gaps that have been covered in the sustainability framework to ensure that the rural libraries will sustain in the community. The objectives of this study were to identify the usage of rural libraries; to understand the challenges faced by rural libraries; to identify environmental sustainability characteristics of rural libraries; to classify economic sustainability characteristics of rural libraries; to recognise social sustainability characteristics of rural libraries; and to develop a sustainability framework of rural libraries. The sustainability issue was in line with the United Nations Agenda in promoting sustainability worldwide. Six (6) rural libraries in Peninsular Malaysia were selected for this study, whereby the staff, users and non-users were interviewed. This study employed qualitative approach as it is the best method to understand phenomenon, and answering questions. The semi-structured interviews used as it provides flexibility to the researcher in collecting the data. ATLAS.ti version 7 is used in analysing the data. This study identified the characteristics of the sustainability elements, namely environmental, economic and social, alongside two (2) new findings on the Malaysian rural libraries’ sustainability. This study proposed a framework for rural libraries' sustainability consisting of five (5) elements namely environment, economic, social, financial and intellectual capital. This study contributes to the establishment of new guidelines for rural libraries' sustainability through the framework proposed. This new framework produced three major contributions and implications consist of professional contributions, theoretical contributions and community contributions. The recommendation for future research includes large numbers of rural libraries in order to get accurate results, each rural library has its own sub-elements of their framework, and extends the research to states rural libraries.